Optimization of Irrigation in Crambe (Crambe abyssinica) for Enhancing Biofuel Production - Silva, Alison Batista da; Mata, Djair Alves da; Souza, Francisca Iris da Silva; Oliveira, Ana Cecília da Rocha; Macena, Romildo Araújo; Silva, Geiziane de Fátima da; Medeiros, Thayná Kelly Formiga de; de Medeiros, Aline Carla; Maracajá, Patrício Borges (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
Crambe (Crambe abyssinica), from the Brassicaceae family and native to the Mediterranean region, stands out as a promising agroenergy crop. Its large-scale cultivation occurs mainly in Mexico and the USA, having been introduced to Brazil in 1995. The demand for sustainable energy sources is growing due to the finite nature of petroleum, with vegetable oils serving as alternatives for biodiesel production, helping reduce CO₂ emissions. Crambe has a short cycle (90 days), seed yield of 1,000–1,500 kg ha⁻¹, low production cost, and high oil content (26–38%), with industrial applications and useful by-products. Optimizing irrigation in crambe cultivation is key to enhancing biofuel production by assessing the impact of irrigation intervals on agronomic performance. A field experiment was conducted at UEPB (Lagoa Seca, PB, Brazil) under a humid tropical climate, in Eutrophic Regolithic Neosol. The experimental design was a randomized block, in a 3×4 factorial arrangement (irrigation intervals: 1, 2, and 3 days; 4 replications), with plots of 20 m². Irrigation was performed by drip system, based on water balance, with fertilization using 30 t ha⁻¹ of cattle manure, cultivar FMS Brilhante. The following traits were evaluated at 60 and 75 days after sowing: plant height, stem diameter, leaf area, number of branches, number of capsules, biomass, thousand-seed weight, and yield. Data were analyzed by ANOVA, Tukey test (5%), and regression using SISVAR. An irrigation interval of 1 day increased plant height (1.05 m), number of branches (10.25), leaf area (148.15 cm²), thousand-seed weight (7.37 g), and yield (297.31 kg ha⁻¹). The 2-day interval improved stem diameter (7.18 mm), thousand-seed weight (7.90 g), and biomass (13.98 g/plant). The 3-day interval increased the number of capsules (549.88), but reduced yield (212.80 kg ha⁻¹).